THE NEEDS ANALYSIS OF ENGLISH MATERIAL ON CHEMICAL INDUSTRY STUDENTS - Iin Widya Lestari; Adi Isma (English Study Program University of Pasir Pengaraian, 2018)
This research aims to find out the students need at chemical industry major at SMKN 2 Bojonegoro. This is classified as mixed method research design. It used two kinds of instruments namely questionnaire and interview guidelines. The questionnaire aims to gain and collect information from students especially their need related to English teaching and learning. While, interview guideline is used to gather information from English teacher at SMKN 2 Bojonegoro. The result shows that there are some skills and language components that students need at chemical industry major such as; listening, speaking, vocabulary, and grammar. Based on the data obtained from questionnaire, most of students say that listening and speaking are two important skills and needed at chemical industry major. While at school, the ESP approach is not applied yet, as a result, it influences on choosing materials. It can be concluded that in designing materials, the teachers and curriculum maker should do needs analysis and analyze what actually students need and work need.